The need for revision of selected aspects of online Master's and doctoral student supervision - Karen Ferreira-Meyers (Perspectives in Education, 2022)
Since the onset of the COVID-19 pandemic, higher education institutions have been concerned about their Master and doctoral students, in particular how and when they would be able to continue and complete their research activities and dissertations. Scholars have noted the potential deterioration in the quality of research projects for a variety of reasons (transformation and/ or abandoning of approved research methods, anxiety-related lowered performance rates, altered modes of supervision and delays in completion times). In this article, I discuss the findings of a small-scale study, undertaken in July 2020, on whether there has been a significant change in the supervision of Master’s and doctoral students in Africa due to the outbreak and impact of the COVID-19 pandemic. I used a Google Form online survey to obtain participants’ opinion on the frequency of interactions between supervisors and supervisees, the medium of interaction as well as the Master’s and doctoral candidates’ general progress. The study participants were all instructors in higher education who supervise Master and PhD students. There has been a change in frequency and means of supervision, that there is more reliance on videoconferencing tools and interaction “at a distance”. However, the data cannot conclusively confirm that there has been a significant transformation in the way students are supervised because many study participants indicated their wish to return to the way things were done pre-pandemic. Nevertheless, there will probably be more reliance on social media, email and other online tools such as Zoom and Skype post-pandemic. In the words of the study participants, “online supervision is developing” and “the pandemic has also given us more tools of engagement, which is good”.